FOREST MANAGEMENT THROUGH LOCAL WISDOM OF THE COMMUNITY AROUND THE SICIKE-CIKE NATURE PARK, NORTH SUMATRA - Rospita Odorlina P. Situmorang; Elvina R. Simanjuntak (Pusbindiklat - LIPI, 2015)
The presence of local wisdom in Sicike-Cike Nature Park, North Sumatra, was studied. The result shows that local wisdom is important in forest conservation and tourism related purposes. The result also indicates that the conservation of The Nature Park and its water source is also supported by the existence of traditionalcustoms still largely followed and believe in nature as a sacred area.The preservation of forest management in The Nature Park through local wisdom is influenced by three group factors: basic factor, supporting, and motivating.Co-management that incorporates both local people and goverment is regarded as the best solution offered in the forest management of Sicike-Cike Nature Park.